2009
DOI: 10.1002/ptr.2924
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic evidence of mandibular osteoporosis improvement in Wistar rats treated with Ginkgo biloba

Abstract: The EGb recovered the periodontal bone support and increased the mandibular cortical thickness. The EGb may be effective in the treatment of osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…Recently, studies of G. biloba in osteoporosis and bone metabolism have shown promising results stimulating osteoblast differentiation (Brayboy et al , ; Oh et al , ). Also, Trivedi et al () reported that EGb improved bone mineral density in ovariectomized rats, in the same way that in our previous studies EGb improved periodontal bone support and the percentage of alveolar bone support in the mandible and trabecular bone in femur of rats with GIO (Lucinda et al , ,).…”
Section: Introductionsupporting
confidence: 75%
See 3 more Smart Citations
“…Recently, studies of G. biloba in osteoporosis and bone metabolism have shown promising results stimulating osteoblast differentiation (Brayboy et al , ; Oh et al , ). Also, Trivedi et al () reported that EGb improved bone mineral density in ovariectomized rats, in the same way that in our previous studies EGb improved periodontal bone support and the percentage of alveolar bone support in the mandible and trabecular bone in femur of rats with GIO (Lucinda et al , ,).…”
Section: Introductionsupporting
confidence: 75%
“…G. biloba is a plant that is currently being used by the population for its therapeutic properties; however, very little is known about its effects in osteoporosis because of the lack of preclinical and absence of clinical studies. The preclinical studies suggest that EGb is a promising therapy to recover bone loss in estrogen depletion osteoporosis (Trivedi et al , ; Oh et al , ) and in the GIO (Lucinda et al , , ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Computer‐aided design program ‖‖‖ measurements were calibrated by the standard lead bar length on the radiograph. Three points on the radiographs were considered as shown in Figure 2, that is, the apex of the distal/mesial root (A), the crest bone on the distal/mesial surface of the tooth (B), and the tip of the distal/mesial cusp (C) according to the method described by Lucinda et al 30 The linear distances between AB and AC points were measured to calculate the periodontal bone support near the root using the following mathematical formula: AB/AC × 100 31 …”
Section: Methodsmentioning
confidence: 99%